REINTERPRETASI HADIS TENTANG KEUTAMAAN BULAN RAJAB, SYA’BAN DAN RAMADAN - Muhammad Nuh Siregar (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“Islamic societies generally practice fadilah charity in certain months. Indeed in Islam it is strongly recommended to implement fadhilah charity (virtue of charity). But in carrying out fadilah charity must be based on the Qur'an and the Hadith of the Prophet. Hadith of the Prophet who became the foundation of worship is certainly must be qualified sahih and hasan. Some scholars there are those who think that the Hadith can be practiced in the matter of fadilah charity. But his naivete status is not too daif. The point is the quality of his sanad or narration Hadith no one is charged with munkar and the equivalent of it.”